Perubahan Sosial Ekonomi Masyarakat Pesisir Pada Masa Pandemi Corona Virus Diseases of 2019 (Covid-19) - Ratna Rahmawati; Syech Hariyono; Sari Dewi Poerwanti (Jurnal Intervensi Sosial dan Pembangunan, 2023)
Socio-economic change is a behavioral adaptation based on influence, assistance and internalization of people who accept new attitudes and have the same values as before to move from certain conditions to other conditions. This shows that socio-economic change is one of the processes of change experienced by humans based on what has been learned and is largely determined by the conditions and needs of each individual. Therefore, the socio-economic changes that occur affect the socio-economic factors of coastal communities due to the Covid-19 pandemic. This phenomenon encourages us to be able to find out about the socio-economic changes that have occurred in the coastal communities of Payangan Beach, Watu Ulo Hamlet, Sumberejo Village, to improve their welfare for the better during the Covid-19 pandemic. This study is a descriptive qualitative research, data obtained from semi-structured interviews, non-participatory observation, and documentation. Determination of informants and locations using snowball sampling technique. Then analyzed systematically through the stages of data collection, data reduction, data presentation, as well as drawing conclusions and verification. Researchers used the source triangulation technique. The results of this study indicate that socio-economic changes in coastal communities have decreased income, hampered the work of coastal communities, and changes in the education of school children in Payangan, Jember Regency during the Covid-19 pandemic.Keywords: Socioeconomic Change, Coastal Communities, Covid-19Socio-economic change is a behavioral adaptation based on influence, assistance and internalization of people who accept new attitudes and have the same values as before to move from certain conditions to other conditions. This shows that socio-economic change is one of the processes of change experienced by humans based on what has been learned and is largely determined by the conditions and needs of each individual. Therefore, the socio-economic changes that occur affect the socio-economic factors of coastal communities due to the Covid-19 pandemic. This phenomenon encourages us to be able to find out about the socio-economic changes that have occurred in the coastal communities of Payangan Beach, Watu Ulo Hamlet, Sumberejo Village, to improve their welfare for the better during the Covid-19 pandemic. This study is a descriptive qualitative research, data obtained from semi-structured interviews, non-participatory observation, and documentation. Determination of informants and locations using snowball sampling technique. Then analyzed systematically through the stages of data collection, data reduction, data presentation, as well as drawing conclusions and verification. Researchers used the source triangulation technique. The results of this study indicate that socio-economic changes in coastal communities have decreased income, hampered the work of coastal communities, and changes in the education of school children in Payangan, Jember Regency during the Covid-19 pandemic. Keywords: Socioeconomic Change, Coastal Communities, Covid-19